42 Negative correlation between PlGF and Endocan-1 in women with preeclampsia - Ribeiro Hentschke, Marta; Mistry, Hiten D.; Ercilia Pinheiro da Costa, Bartira; Poli-de-Figueiredo, Carlos Eduardo (Elsevier, 2016)
Introduction: Endocan-1 is a soluble proteoglican specifically expressed in endothelial cells, a biomarker/predictor of vascular endothelial related pathologies, as pre-eclampsia (PE). PlGF is an angiogenic factor, and a marker of placental dysfunction, which is down regulated in women with PE. We hypothesized that Endocan-1 and PlGF levels would be negatively correlated in pregnant women with PE. Objectives: To analyse Endocan-1 and PlGF levels in maternal plasma in normotensive and women with PE and test the correlation between the findings in the third trimester of pregnancy. Methods: Endocan-1 and PlGF levels were measured in maternal plasma from normotensive (n= 67) and PE (n= 50) women using MagPlexTH-C microspheres system. Data was analysed by ANCOVA, adjusted for BMI, gestational age and maternal age. To estimate the difference between groups, mean ratio (MR) and confidence interval (CI) of 95% was calculated. Analysis between Endocan-1 levels and PlGF were made by Pearson correlation. The null hypothesis was rejected when p < 0.05. Results: Higher concentrations of Endocan-1 were found in maternal plasma in PE (MR = 1.49; 95% CI: 1.19–1.85,p= 0.001), with a moderate effect size (Cohen’s D = 0.84). When women with superimposed PE and HELLP syndrome were excluded, lower levels of PlGF were found in the PE group (MR = 0.38, 95% CI: 0.15–0.95 p = 0.041). A strong negative correlation between Endocan-1 e PlGF in the entire group (r=-0.605; p < 0.001); as well as in PE group (r=-0.545; p < 0.001) was observed. Conclusion: Endocan-1 levels are increased in patients with PE and are negatively correlated with PlGF levels. These data could be related to hypoxemia and fetal growth restriction (seen by lower PlGF levels), leading to a systemic response in order to find a volumetric compensation; leading to endothelial lesions (seen as the upregulation of Endocan-1). Thus, it is important to analyse angiogenic and proinflamatory molecules concomitantly in women with PE, in order to better understand the disease pathophysiology. In this case, both molecules are strong potentials as specific PE biomarkers.